Effect of Demographic Transition on The Needs of Foreign Workers in Japan - Ngurah Indra Pradhana (KIRYOKU, 2022)
This research is entitled, "The Effect of Demographic Transition on the Needs for Foreign Workers in Japan". The data from this study are from the distribution of questionnaires to students at Kobe Women's University-Japan and the results of interviews from a number of informants in Japan. From the distribution of the questionnaire, there were 70 data related to this research. Specifically, the purpose of this study is to answer the Japanese public's response to the need for foreign workers in Japan and the type of work that dominates foreign workers in Japan. This research will be studied from a socio-cultural point of view. The method used is an open questionnaire and a closed questionnaire with an advanced technique, namely interviews. The results of this study are that of the 70 informants, 60 people responded that Japan was being dominated by foreign workers and 10 more people said they did not agree with the statement. Regarding the dominant occupations carried out by foreign workers in Japan, among others, health workers for the elderly, manufacturing, shopkeepers who are open until late, and restaurants. The point is that it is a job field that is rarely liked by Japanese people and for foreign workers who do not use Japanese much while working. However, foreign workers who want to work in Japan should understand the culture and customs of Japanese society.